Electrochromism of Ni(OH)2 films obtained by cathode template method with addition of Al, Zn, Co ions - Kotok, Valerii; Kovalenko, Vadym (Eastern-European Journal of Enterprise Technologies, 2017)
The films from mixed solutions of nickel-aluminum, nickel-zinc and nickel-cobalt have been prepared using the cathodic template synthesis with polyvinyl alcohol as a template. The prepared films have been studied by means of X-ray diffraction analysis, cyclic voltamperometry with simultaneous recording of the transparency change. The results have shown that the addition of aluminum and cobalt allows obtaining layered double hydroxides. However, the addition of aluminum leads not only to the formation of layered double hydroxide but also to poisoning of the active material. In case of deposition from solutions containing cobalt, the obtained films have good electrochemical and electrochromic properties, and also two-stage color transition. The film obtained at a molar ratio of nickel to cobalt of 8:1 possesses the best electrochromic characteristics and coloration degree of 0.8, which is more than for the film obtained from nickel nitrate solution without additives of other metals by 0.2.